Long-Term Follow-Up of Refractory Large Macular Hole with Autologous Neurosensory Retinal Free Flap Transplantation. (9th May 2022) - Lee, Po-Yen; Chang, Yo-Chen; Liu, Pei-Kang; Kao, Tzu-En; Wu, Horng-Jiun; Chen, Kuo-Jen; Wu, Kwou-Yeung; Cheng, Kai-Chun; Wu, Wen-Chuan
Abstract : Purpose . To evaluate the long-term anatomic and functional outcomes of autologous neurosensory retinal free flap transplantation (ART) for patients with refractory large macular hole (MH). Design . Retrospective interventional case series. Methods . We reviewed 9 patients who underwent ART for their refractory large MH. In this extended follow-up study, postoperative assessment including spectral-domain optical coherence tomography and best-corrected visual acuity (BCVA) were recorded at 12, 15, 18, 21, and 24 months after surgery. Results . The macular hole of all patients appeared successfully closed during the whole follow-up period. The mean logMAR BCVA improved from 1.61 ± 0.44 (preoperative) to 0.72 ± 0.30 (12 months after surgery) (p < 0.001 ). Thereafter, the mean BCVA remained stable at each follow-up. At the mean 16.0 ± 0.8 months postoperatively, inner retinal cystic changes were observed in 4 eyes (44.4%), but these did not significantly affect vision. Conclusion . ART is a good alternative technique for closing large refractory macular holes. Although inner retinal cystic changes were observed in 4 eyes (44.4%), this phenomenon did not significantly affect visual acuity. It provides long-term good anatomical and functional results, especially in cases where insufficient ILM or lens capsule are left.